Is stump harvesting for bioenergy production socially acceptable in Finland?. (20th August 2019) - Rahman, Abul; Khanam, Tahamina; Pelkonen, Paavo
Abstract: Stump wood is used to produce electricity and heat, especially in Finland, where biomass-based energy plays a major role. This study, which aims to investigate the social acceptance of stump harvesting for bioenergy production in Finland, was conducted in two stages: a questionnaire-based study and a subsequent literature-based study. The latter provides information concerning the beneficial or harmful consequences of stump harvesting, and this information could be used to gain support for stump harvesting's use or abandonment by stakeholders of forest utilisation. The questionnaire survey was conducted in 2013 at the SILVA fair organised by the Association of Finnish Forestry centre in Joensuu, Finland, and the literature-based study was conducted in 2018. Six social groups were defined: higher administrative, lower administrative, skilled or specialized workers, farm and forestry workers, students, and others. The results of the questionnaire revealed that, although different social groups are highly interested in using stump wood for energy purposes, respondents think that stump harvesting will not be able to raise their incomes. Respondents are also unmotivated, with even forestry workers expressing critical views on the promotion of stump harvesting for energy purposes due to the environmental consequences. The literature-based study revealed that scientific results on stump harvesting are contradictory. It is crucial to involve different social groups and to reflect on their opinions regarding the use of stump wood as a forest management tool and for bioenergy production. As Finland moves toward a bioeconomy, the study of social acceptance of stump harvesting will direct the development of stump harvesting for bioenergy production.